Prayer as Seeing: An Exploration of the Aesthetics of Contemplation and Glossolalia - Kamenicky, Michael Austin (Journal of pentecostal theology, 2021)
Abstract This article provides a theological framework whereby the practices of silent contemplative prayer and tongues speech can be understood as mutually conditioning prayer practices that form the one who prays to perceive both beauty and the beautiful. It does so through an examination of the implicit metaphysical assumptions of the respective practices. The first section examines the implicit relationship between contemplative prayer and divine impassibility. The second section examines the relationship between glossolalia and divine relationality. The third section presents the practices of contemplation and glossolalia as mutually informative in dialogue with Gregory Palamas’ distinction between divine essence and energies. The article will therefore conclude that a comprehensive prayer practice that unites the experiences of impassibility and relationality can overcome the aesthetic divide between the mystical and the artistic by uniting the one who prays with a God who is both transcendent and relational.